Associations between maternal inflammation during pregnancy and infant birth outcomes in the Seychelles Child Development Study. (February 2020) - Yeates, A.J.; McSorley, E.M.; Mulhern, M.S.; Spence, T.; Crowe, W.; Grzesik, K.; Thurston, S.W.; Watson, G.E.; Myers, G.J.; Davidson, P.W.; Shamlaye, C.F.; van Wijngaarden, E.; et al.
Highlights: Maternal Th1, Th2 and Th1:Th2 ratio at 28 weeks gestation, were not associated with infant birthweight, birth length or head circumference. Higher concentrations of vascular endothelial growth factor D (VEGF-D) are predictive of a lower birthweight and length. Higher concentrations of C-Reactive Protein (CRP), a pro-inflammatory marker, were associated with a lower birthweight. A longer gestational age was predicted by higher concentrations of monocyte chemotactic protein-1 (MCP-1) and interleukin 2 (IL-2). Further research is required to aid understanding of the importance of these findings. Abstract: Problem: Markers of maternal inflammation may determine infant birth outcomes. Method of study: Maternal serum samples were collected at 28 weeks gestation ( n  = 1418) in the Seychelles Child Development Study Nutrition Cohort 2 and analyzed for immune markers by MSD multiplex assay, including cytokines from the Th1 (IFN-γ, IL-1β, IL-2 and TNF-α) and Th2 (IL-4, IL-5, IL-10) subsets, with IL-6, MCP-1, TARC, sFlt-1 and VEGF-D. Associations of log-transformed immune markers with birthweight, length, head circumference and gestational age were assessed by multiple linear regression models, which were adjusted for maternal age, BMI, parity, child sex, gestational age and socioeconomic status. Results: Neither total Th1, Th2 nor Th1:Th2 were significantly associated with any birth outcome. However, the angiogenesis marker VEGF-D was predictive of a lower birthweight, (β = −0.058, P  = 0.017) and birth length (β = −0.088, P  = 0.001) after adjusting for covariates. Higher concentrations of CRP were predictive of a lower birthweight (β = −0.057, P  = 0.023) and IL-2 (β = 0.073, P  = 0.009) and the chemokine MCP-1 (β = 0.067, P  = 0.016) were predictive of a longer gestational age. Conclusions: In our cohort of healthy pregnant women, we found no evidence for associations between the Th1 or Th2 inflammatory markers with birth outcomes. However, VEGF-D and CRP appear to predict lower birthweight and IL-2 and MCP-1 a longer gestation. Greater understanding is required of the variation in these immune markers at different gestational stages, as well as the factors which may regulate their balance in healthy pregnancy. n = 233 .